Problems met in lesson planning by the pre-service teachers - Joel Cayabyab Ferrer (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study attempted to evaluate the problems met in lesson planning by the pre-service teachers of Ilocos Sur Polytechnic State College, Sta. Maria Main Campus, Philippines during the three consecutive School Years from 2018-2020. The descriptive survey method with the questionnaire constructed by the researcher was the main data instrument with a reliability coefficient of 0.81. Total enumeration was employed with 108 cooperating teachers from six (6) different public elementary schools and 114 pre-service teachers. Findings of the study revealed that respondents find the formulation objectives, selection of subject matter, and implementation stage as slightly serious. On the significant difference in the problems met in lesson planning by the students and the teachers, there exist a significant difference along with the area on Assignment. A correlation between the planning and implementation stage or vice versa was also found out.